Stone Ossuaries in the Hecht Museum Collection and the Issue of Ossuaries Use for Burial - Guri-Rimon, Ofra (Journal of Hellenistic Pottery and Material Culture, 2017)
The ﬁrst part of the article is devoted to the publication of four stone ossuaries in the Hecht Museum collection, thereby joining them to the rich and varied assemblage of stone ossuaries that have been published up to now. The second part of the article relates to the use of stone ossuaries for burial purposes toward the end of the Second Temple period. I present an argument with regard to this issue that has not been advanced to this day: the custom of burial in ossuaries bears a relationship to the Jewish ritual laws (halacha) of uncleanness and purity similar to the aﬃnity between these laws and stone vessels.